2019
DOI: 10.1007/s11306-019-1511-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite and transcript profiling of Guinea grass (Panicum maximum Jacq) response to elevated [CO2] and temperature

Abstract: IntroductionBy mid-century, global atmospheric carbon dioxide concentration ([CO2]) is predicted to reach 600 μmol mol−1 with global temperatures rising by 2 °C. Rising [CO2] and temperature will alter the growth and productivity of major food and forage crops across the globe. Although the impact is expected to be greatest in tropical regions, the impact of climate-change has been poorly studied in those regions.ObjectivesThis experiment aimed to understand the effects of elevated [CO2] (600 μmol mol−1) and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 63 publications
(81 reference statements)
0
29
0
3
Order By: Relevance
“…Meanwhile, under warming and irrigated plots (eTiR), we observed an increase in leaf dry biomass production. This beneficial effect of warming was presumably associated with a higher leaf homeostatic capacity (Olivera‐Viciedo et al., 2019), a higher content of amino acids related to drought tolerance (Wedow et al., 2019), a higher accumulation of N, P, K and Ca (Figure 4a‐d), B, Cu, Fe, Mn (Figure 5a‐d) and an increase in the NUE of macronutrients (Figure 6a‐e), and micronutrients as Cu, Mn and Zn (Figure 7b, d, e). In addition, a greatest root growth under eTiR condition (Figure 3b‐e) was also found and this synchronization between shoot and root growth is necessary since a greater aerial growth increases the demand for more water and nutrient uptake from soil (Hodge et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, under warming and irrigated plots (eTiR), we observed an increase in leaf dry biomass production. This beneficial effect of warming was presumably associated with a higher leaf homeostatic capacity (Olivera‐Viciedo et al., 2019), a higher content of amino acids related to drought tolerance (Wedow et al., 2019), a higher accumulation of N, P, K and Ca (Figure 4a‐d), B, Cu, Fe, Mn (Figure 5a‐d) and an increase in the NUE of macronutrients (Figure 6a‐e), and micronutrients as Cu, Mn and Zn (Figure 7b, d, e). In addition, a greatest root growth under eTiR condition (Figure 3b‐e) was also found and this synchronization between shoot and root growth is necessary since a greater aerial growth increases the demand for more water and nutrient uptake from soil (Hodge et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, under heating, there was no increase in photosynthesis and transpiration [6,13], suggesting that under a warmed atmosphere, P. maximum may exhibit increased NUE. It was also observed that under heating, P. maximum exhibited an increase in the concentration of many amino acids, such as valine, threonine and phenylalanine, which have N in their structure [14]. In addition, warming may stimulate nutrient uptake through increased root system growth, increased nutrient diffusion rates and water in-flow [15] but at the same time, gain in dry mass on heating may result in a leaf N dilution effect in P. maximum [11].…”
Section: Introductionmentioning
confidence: 94%
“…Field metabolomics can be a powerful approach for profiling the metabolite changes in plants in response to environmental stress (Melandri et al., 2020; Wedow et al., 2019). The physiological response of crops to O 3 pollution has been well studied, with elevated [O 3 ] decreasing carbon assimilation, accelerating senescence and cell death, and reducing economic yield (Ainsworth, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…More broadly, metabolomics provides a tool to explore biochemical signatures that may be predictive of environmental stress effects on primary productivity, even in field conditions. Studies have examined the relationship between leaf metabolites and physiological traits in the field under various abiotic stress conditions in maize (Obata et al., 2015; Riedelsheimer et al., 2012), rice (Melandri et al., 2020), and Guinea grass (Wedow et al., 2019). Additionally, metabolomics has been used to identify markers associated with greater yield potential in maize (Cañas et al., 2017).…”
Section: Introductionmentioning
confidence: 99%